2021
DOI: 10.1017/cjn.2021.155
|View full text |Cite
|
Sign up to set email alerts
|

Airway Management with Leksell Frame in situ with or without Frontal Bar: A Mannequin Study

Abstract: Background: The use of stereotactic headframes for neurosurgical procedures requiring targeted localization continues to grow with new advancements in technology and treatment modalities. A configuration of the Leksell stereotactic G frame with a straight front bar, useful in epilepsy and laser cases, almost completely obscures oral access and presents a significant airway challenge for the anesthetist. Although previous papers have suggested that the entire headframe should be removed during an airway em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The stereotactic headframe used to stabilize the head and neck during stereotactic brain surgery makes accessing the airway a challenge, and conventional DL is of limited use in such scenarios [ 42 , 43 ]. Few studies proposed alternative airway management modalities, including using a flexible FOB, an intubating laryngeal mask airway (ILMA), a gum elastic bougie, a lightwand (e.g., Trachlight™), and videolaryngoscopy (VL) in some difficult airway scenarios [ 44 , 45 , 46 , 47 , 48 ]. The airway operators should know in advance that the in-place headframe may make it difficult to access the upper airway and thus have a contingency plan to handle the airway, should the need unexpectedly arise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stereotactic headframe used to stabilize the head and neck during stereotactic brain surgery makes accessing the airway a challenge, and conventional DL is of limited use in such scenarios [ 42 , 43 ]. Few studies proposed alternative airway management modalities, including using a flexible FOB, an intubating laryngeal mask airway (ILMA), a gum elastic bougie, a lightwand (e.g., Trachlight™), and videolaryngoscopy (VL) in some difficult airway scenarios [ 44 , 45 , 46 , 47 , 48 ]. The airway operators should know in advance that the in-place headframe may make it difficult to access the upper airway and thus have a contingency plan to handle the airway, should the need unexpectedly arise.…”
Section: Discussionmentioning
confidence: 99%
“…A mannequin study showed that intubating with VL under an ideal situation for the Leksell front bar in situ is possible [ 48 ]. To remove just the front bar is a simpler and more streamlined approach to provide a quicker airway control in case of emergency.…”
Section: Discussionmentioning
confidence: 99%
“…Adding extensions to the anesthesia circuit and the intravenous tubing may be necessary. If an accidental extubation occurs, placement of an LMA may be the best rescue device, given the limitations of working in a magnetic field [12].…”
Section: Therapeutic Modalitiesmentioning
confidence: 99%
“…Perhaps most significant is that the frame itself is made of a nonmetallic, glass fiber–reinforced epoxy composite material that limits both MRI and computed tomography (CT) artifact, purportedly enhancing the fidelity of preoperative imaging. 1 The Vantage frame also lacks the G frame's front cross-bar, which blocks the patient's face, providing easier airway access in the event of an emergency 2 and allowing for better visualization of the patient's face, which can be beneficial during awake surgeries. The elimination of the front bar also increases patient comfort, as does the elimination of the G frame's notoriously uncomfortable ear bars, which are used during frame application.…”
mentioning
confidence: 99%